1990
DOI: 10.3382/ps.0690845
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Hepatomegaly Induced by the Pulsatile, but not Continuous, Intravenous Administration of Purified Chicken Growth Hormone in Broiler Pullets: Liver Composition and Nucleic-Acid Content

Abstract: The present study determined the composition and nucleic-acid content of livers obtained from 11-wk-old, broiler-strain pullets infused with pituitary-derived chicken growth hormone (p-cGH) in either a pulsatile (Study 1) or continuous (Study 2) manner for 21 days. Pulsatile p-cGH administration resulted in a decrease in ratios for liver DNA to wet weight (P less than .01), DNA to protein (P less than .03), and DNA to RNA (P less than .002), compared with controls. Total RNA-to-liver ratio (P less than .003) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, transgenic mice over‐expressing GH have been reported to have selective splanchnomegaly coupled with hepatomegaly (39), and others have reported that GH‐transgenic mice have accelerated liver, kidney, and skeletal growth (40). Finally, pulsatile administration of GH in broiler pullets induced hepatomegaly largely due to cellular hypertrophy (41). On the other hand, diphtheria toxin–induced GH deficiency caused a 24% reduction in the relative liver size (42).…”
Section: Effects Of Total Igf‐1 Deficiencymentioning
confidence: 99%
“…Furthermore, transgenic mice over‐expressing GH have been reported to have selective splanchnomegaly coupled with hepatomegaly (39), and others have reported that GH‐transgenic mice have accelerated liver, kidney, and skeletal growth (40). Finally, pulsatile administration of GH in broiler pullets induced hepatomegaly largely due to cellular hypertrophy (41). On the other hand, diphtheria toxin–induced GH deficiency caused a 24% reduction in the relative liver size (42).…”
Section: Effects Of Total Igf‐1 Deficiencymentioning
confidence: 99%